If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 11y = 18 Solving 12x + 11y = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. 12x + 11y + -11y = 18 + -11y Combine like terms: 11y + -11y = 0 12x + 0 = 18 + -11y 12x = 18 + -11y Divide each side by '12'. x = 1.5 + -0.9166666667y Simplifying x = 1.5 + -0.9166666667y
| 4b+3-b=4(b-5)+2 | | 0.4(p+1)-0.9(p+5)=-2 | | (2x^2+3x-6)-(x^2-18x+6)= | | -250+5(5)= | | 6(7x+9)=264 | | 6(3+k)=48 | | c-(-75)=25 | | -250+5(3)= | | 4(h+8)=16 | | 6-4u=2 | | a(6a^2+2a+9)= | | 6(2-x)=20 | | 21-11y=7 | | 2x-10(2x-1)=5 | | 0.5x+58=-23 | | 7y=210 | | -6x-7=29 | | 250=x*1000 | | 6x+2x-5=43 | | (X-3)(X+3)=6x^2-14 | | 5+3(4x-2)=-18 | | a+7=11 | | 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= | | 1.5=x*11 | | 5e-14=8 | | 4n(-n^3-4n+1)= |